A Look Back: Evolving views on parental engagement in schools. (April 2022) - Preston, Teresa
Educators have long agreed that parents have a role to play in furthering their children's education, but they have not always agreed about what the nature of that role should be or about how schools can develop more productive relationships with parents. In this monthly column, Teresa Preston traces how that debate has played out in Kappan. Authors have debated how much schools have historically wanted parents to participate in their children's education, and they've explored how schools should respond when parents do not or cannot participate .